Pedagogical and Political Activity of Pēteris Sauleskalns (1876–1975), a Graduate (1908) of Riga Polytechnic Institute - Zvirgzdiņš, Indulis (History of Engineering Sciences and Institutions of Higher Education, 2022)
In the study dedicated to Pēteris Sauleskalns (1876–1975), a graduate of Riga Polytechnic Institute (RPI), an agronomist, pedagogue, and teacher, the author used archival and library materials describing the family of Sauleskalns and the childhood of his son Pēteris, his study and work life, and pedagogical activities at Priekuļi (1912–1918) and Latgale (1921–1936) / Malnava (1936– 1940) Agricultural Secondary Schools, evaluating his contribution to the establishment and management of the Malnava Agricultural Secondary School. The teacher with a long-term experience, P. Sauleskalns also participated in political life – he represented the Latvian Farmers’ Union at the Latvian Constitutional Assembly (1920–1922). For his successful work in the area of agricultural education, he was twice awarded the highest Latvian state award – the Order of the Three Stars. After World War II, he lived in exile in the United States.